Twelve-Month Outcomes of a Group-Randomized Community Health Advocate-Led Smoking Cessation Intervention in Public Housing. Issue 12 (14th November 2017) - Brooks, Daniel R; Burtner, Joanna L; Borrelli, Belinda; Heeren, Timothy C; Evans, Tegan; Davine, Jessica A; Greenbaum, Jonathan; Scarpaci, Matthew; Kane, John; Rees, Vaughan W; Geller, Alan C
Abstract: Background: Lower rates of smoking cessation are a major reason for the higher prevalence of smoking among socioeconomically disadvantaged adults. Because barriers to quitting are both more numerous and severe, socioeconomically disadvantaged smokers may benefit from more intensive intervention. We sought to determine whether a smoking cessation intervention delivered by public housing residents trained as Tobacco Treatment Advocates (TTAs) could increase utilization of cessation resources and increase abstinence. Methods: We conducted a group-randomized trial among Boston public housing residents who were interested in quitting smoking. Participants at control sites received standard cessation materials and a one-time visit from a TTA who provided basic counseling and information about cessation resources. Participants at intervention sites were eligible for multiple visits by a TTA who employed motivational interviewing, cessation counseling, and navigation to encourage smokers to utilize cessation treatment (Smokers' Quitline and clinic-based programs). Utilization and 7-day and 30-day point prevalence abstinence were assessed at 12 months. Self-reported abstinence was biochemically verified. Results: Intervention participants ( n = 121) were more likely than control participants ( n = 129) to both utilize treatment programs (adjusted odds ratio [aOR]: 2.15; 95% confidence interval [CI]: 0.93–4.91) and 7-day and 30-day point prevalence abstinence (aOR: 2.60 (1.72–3.94); 2.98 (1.56–5.68), respectively). Mediation analysis indicated that the higher level of utilization did not explain the intervention effect. Conclusions: An intervention delivered by peer health advocates was able to increase utilization of treatment programs and smoking abstinence among public housing residents. Future studies of similar types of interventions should identify the key mechanisms responsible for success. Implications: In order to narrow the large and growing socioeconomic disparity in smoking rates, more effective cessation interventions are needed for low-income smokers. Individual culturally-relevant coaching provided in smokers' residences may help overcome the heightened barriers to cessation experienced by this group of smokers. In this study among smokers residing in public housing, an intervention delivered by peer health advocates trained in motivational interviewing, basic smoking cessation skills, and client navigation significantly increased abstinence at 12 months. Future research should address whether these findings are replicable in other settings both within and outside of public housing.